Depathologising gender diversity in childhood in the process of ICD revision and reform. Issue 11 (2nd November 2018) - Suess Schwend, Amets; Winter, Sam; Chiam, Zhan; Smiley, Adam; Cabral Grinspan, Mauro
ABSTRACT: From 2007 on, the World Health Organisation (WHO) has been revising its diagnostic manual, the International Statistical Classification of Diseases and Related Health Problems (ICD), with approval of ICD-11 due in 2018. The ICD revision has prompted debates on diagnostic classifications related to gender diversity and gender development processes, and specifically on the 'Gender incongruence of childhood' (GIC) code. These debates have taken place at a time an emergent trans depathologisation movement is becoming increasingly international, and regional and international human rights bodies are recognising gender identity as a source of discrimination. With reference to the history of diagnostic classification of gender diversity in childhood, this paper conducts a literature review of academic, activist and institutional documents related to the current discussion on the merits of retaining or abandoning the GIC code. Within this broader discussion, the paper reviews in more detail recent publications arguing for the abandonment of this diagnostic code drawing upon clinical, bioethical and human rights perspectives. The review indicates that gender diverse children engaged in exploring their gender identity and expression do not benefit from diagnosis. Instead they benefit from support from their families, their schools and from society more broadly.